A Framework for Designing Training Programs to Foster Self-Regulated Learning and Text Analysis Skills. (10th August 2014) - Wagner, Daniela; Dörrenbächer, Sandra; Perels, Franziska
Abstract : The study's aim was to develop an intervention program and to evaluate its contribution to students' self-regulated learning (SRL) and text analysis skills. In a student-focused training approach, the students themselves acquired the training strategies, whereas in the teacher-focused training, the teachers were enabled to explicitly impart these strategies to their students. In order to investigate the effectiveness of the intervention in terms of transfer benefits on SRL and text analysis skills, 274 lower secondary students were examined in a pretest-training-posttest design. Based on two different training approaches, a distinction was made between four groups: student training (singleST), teacher training (singleTT), combination of student and teacher training (ComT), and control group (CG). Substantially more transfer was revealed in all training conditions as compared to the control group. Specifically, the singleST group showed the highest learning gains for all variables. Conversely, a combination of both approaches (ComT) did not result in synergetic effects, but rather in reciprocal interferences.